The C-terminal Tails of the Bacterial Chaperonin GroEL Stimulate Protein Folding by Directly Altering the Conformation of a Substrate Protein - Weaver, Jeremy; Rye, Hays S. (The Journal of biological chemistry, 2014)
Many essential cellular proteins fold only with the assistance of chaperonin machines like the GroEL-GroES system of Escherichia coli. However, the mechanistic details of assisted protein folding by GroEL-GroES remain the subject of ongoing debate. We previously demonstrated that GroEL-GroES enhances the productive folding of a kinetically trapped substrate protein through unfolding, where both binding energy and the energy of ATP hydrolysis are used to disrupt the inhibitory misfolded states. Here, we show that the intrinsically disordered yet highly conserved C-terminal sequence of the GroEL subunits directly contributes to substrate protein unfolding. Interactions between the C terminus and the non-native substrate protein alter the binding position of the substrate protein on the GroEL apical surface. The C-terminal tails also impact the conformational state of the substrate protein during capture and encapsulation on the GroEL ring. Importantly, removal of the C termini results in slower overall folding, reducing the fraction of the substrate protein that commits quickly to a productive folding pathway and slowing several kinetically distinct folding transitions that occur inside the GroEL-GroES cavity. The conserved C-terminal tails of GroEL are thus important for protein folding from the beginning to the end of the chaperonin reaction cycle.